LEGAL CONSEQUENCES OF DELAYING THE IMPLEMENTATION OF AN INTERNATIONAL TREATY - Wafda Vivid Izziyana; Subaidah Ratna Juita; A Heru Nuswato (Universitas Muhammadiyah Ponorogo, 2023)
Two aspects of delays in the implementation of international treaties are delays based on legal subjects or states that are parties to the treaty and delays based on the existence and absence of arrangements in the treaty itself. Whether the delay occurs based on the agreement of all parties or because of the interests of one particular country only. This research method is normative juridical. The results of the study explain the procedures that must be followed if a party proposes a delay in the implementation of an international agreement, regulated in the 1969 Vienna Convention and the UN Charter. Furthermore, the opportunity for the state that proposes a postponement to withdraw its proposal at any time, as long as the proposal has not yet caused any effects or consequences. international agreements that are postponed will certainly have legal consequences both for the agreement itself, the parties, and even in certain cases also for third parties. Parties who agree to postpone are released from the obligations stemming from the treaty in relations between themselves during the postponement period. However, the rights and obligations stemming from the provisions of the treaty continue.